Digital Libraries: Social Media and Community Networks 15th International Conference on Asia-Pacific Digital Libraries, ICADL 2013, Bangalore, India, December 9-11, 2013. Proceedings - Urs, Shalini R.; Na, Jin-Cheon; Buchanan, George (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed proceedings of the 15th International Conference on Asia-Pacific Digital Libraries, ICADL 2013, held in Bangalore, India, in December 2013. The 15 revised full papers, 6 revised short papers, and 10 poster papers were carefully reviewed and selected from 87 submissions. The papers are organized in topical sections on information retrieval; social architecture for digital libraries and information policy; digital library applications and systems; data mining for digital libraries; collaboration and communities; analysing social media and social networks; mobile devices and services; and metadata and information extraction.